Of activism and political resistance. Epistemic (in)justices in the discourses of trans* women: Epistemic (In)justice, a key concept to address trans* memory: The case of the dictatorship and post-dictatorship in Chile (Simbiótica. Revista Eletrônica, 2023)
The life experiences of communities of gender-based dissidence have historically been silenced. This means that the State, its institutions and the social world are unaware of the demands of these groups and their search for justice and reparation. Thanks to the concept of “epistemic injustice” proposed by Miranda Fricker (2017), it is possible to reflect on these types of violence from a perspective that gives us the necessary tools to attend to and address the urgent needs of the LGBTIQA+ population with testimonial sensitivity. Through the work of trans* women’s testimonies, this article seeks to analyze the agentic self-construction of these protagonists, identify their political demands and the responses they have received.
Keywords: epistemic injustice; trans*; LGBTIQA; testimony